2011
DOI: 10.1186/1423-0127-18-24
|View full text |Cite
|
Sign up to set email alerts
|

miR-223 regulates migration and invasion by targeting Artemin in human esophageal carcinoma

Abstract: BackgroundArtemin (ARTN) is a neurotrophic factor belonging to the glial cell-derived neurotrophic factor family of ligands. To develop potential therapy targeting ARTN, we studied the roles of miR-223 in the migration and invasion of human esophageal carcinoma.MethodsARTN expression levels were detected in esophageal carcinoma cell lines KYSE-150, KYSE-510, EC-9706, TE13, esophageal cancer tissues and paired non-cancerous tissues by Western blot. Artemin siRNA expression vectors were constructed to knockdown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 23 publications
1
65
0
4
Order By: Relevance
“…Specifically, patients with lymph node metastasis or metastatic disease at an advanced pathological stage exhibited significantly higher expression of miR-223 compared with patients without lymph node metastasis or (31). However, downregulation of miR-223 has been observed in various types of cancer, including osteosarcoma (32), hepatocellular carcinoma (33) and esophageal carcinoma (34). These previous findings demonstrate that miR-223 may have a vital role as either a tumor suppressor, or as an oncogenic regulator during tumor progression.…”
Section: Discussionmentioning
confidence: 95%
“…Specifically, patients with lymph node metastasis or metastatic disease at an advanced pathological stage exhibited significantly higher expression of miR-223 compared with patients without lymph node metastasis or (31). However, downregulation of miR-223 has been observed in various types of cancer, including osteosarcoma (32), hepatocellular carcinoma (33) and esophageal carcinoma (34). These previous findings demonstrate that miR-223 may have a vital role as either a tumor suppressor, or as an oncogenic regulator during tumor progression.…”
Section: Discussionmentioning
confidence: 95%
“…Activation of MMP-9 and integrin expression in tumor cells mediated the pro-invasive activity of GDNF (Okada et al, 1999). Recently, Li et al (2011) have found that Artemin was a direct target of miR-223 and that miR-223 may have a tumor suppressor function in esophageal carcinoma and could be used in anticancer therapies. Artemin and GFRα3/RET have been proposed as therapeutic agents for pancreatic cancer diseases on the basis of their ability to promote the motility and invasiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence suggests that miR-223 has a role in regulating cell functions, such as proliferation and migration (16,17,22,37). We examined the effect of increased levels of miR-223 on MPM cell proliferation using WST-1 and methylene blue assays.…”
Section: Mir-223 Regulates Mpm Cell Motilitymentioning
confidence: 99%
“…Recent evidence suggests that miR-223 may behave as an oncogene or tumor suppressor in a range of hematopoietic and solid tumors (16)(17)(18)(19)(20)(21) and can regulate functions, such as proliferation, migration (16,22), and chemoresistance (23) in these malignancies. The role of miR-223 in MPM is unknown.…”
Section: Introductionmentioning
confidence: 99%